2013
DOI: 10.1097/brs.0b013e31829a84d2
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic Effects of Aspirin on 1- or 2-Level Lumbar Spinal Fusion Surgery

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…All the concrete information about included studies are listed in Table 1 . [ 5 , 7 , 9 , 10 ] Three studies have lumbar fusion, while 1 study combined cervical, thoracolumbar, and lumbar therapy. Two studies are anticoagulated with aspirin and the other 2 with ASA (they choose aspirin as the representation of ASA).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the concrete information about included studies are listed in Table 1 . [ 5 , 7 , 9 , 10 ] Three studies have lumbar fusion, while 1 study combined cervical, thoracolumbar, and lumbar therapy. Two studies are anticoagulated with aspirin and the other 2 with ASA (they choose aspirin as the representation of ASA).…”
Section: Resultsmentioning
confidence: 99%
“…But some researches point out that the risk of perioperative cardiac events after major noncardiac surgery ranges from 1.4% among the general population older than 50 years of age and increases up to 3.9% in those who are at risk of cardiac disease. [ 7 ] Aspirin decreases the risk of thrombotic events and is the most widely prescribed antiplatelet agent in clinical practice. [ 18 ] A randomized controlled trial showed an absolute risk reduction of 7.2% within 30 days of major noncardiac surgery when aspirin was continued.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspirin should not be taken for at least 1 week before a biopsy is performed, and a biopsy should not be performed for patients who have stopped warfarin until the blood coagulation index is normal. [ 47 ]…”
Section: Transthoracic Core Needle Biopsymentioning
confidence: 99%
“…Several series documented the increased perioperative risks/complications (e.g., hemorrhagic complications, EBL, continued postoperative drainage) when LD-ASA was continued and/or stopped for just 3 up to 7 days preoperatively vs. finding no such risks for LD-ASA stopped for 7–10 (average 9) preoperative days. [ 4 5 ] For patients undergoing 1-level lumbar fusions in Kang et al . (2011), Group 0 were on no LD-ASA, whereas Group 1 patients stopped LD-ASA (100 mg) at least 7 days (average 9 days) preoperatively.…”
Section: Introductionmentioning
confidence: 99%